2008
DOI: 10.1002/app.28067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyurethane nanofibers by electrospinning

Abstract: Polyurethane (PU) nanofibers were prepared by the electrospinning method. The process parameters, including the applied voltage, feeding rate, and solution concentration, were investigated carefully. The results showed that the resultant nanofibers, electrospun from PU/N,Ndimethylformamide (DMF) solutions, had ultrafine diameters ranging from about 700 to 50 nm. In addition, it was found that the diameters and morphology of the nanofibers were influenced greatly by the process parameters. In particular, the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 29 publications
1
79
0
Order By: Relevance
“…Various methods such as wet spun, melt spun, dry spun, and electrospun are used for the production of SMPU fiber [50][51][52][53].…”
Section: Textile Application Of Smpumentioning
confidence: 99%
“…Various methods such as wet spun, melt spun, dry spun, and electrospun are used for the production of SMPU fiber [50][51][52][53].…”
Section: Textile Application Of Smpumentioning
confidence: 99%
“…[19][20][21] Electrospun fibers have been investigated widely [22][23][24] for medical sensors and photonics, 25 41 Due to the high permeability of water vapor at high temperatures and considerably lower permeability capacity at lower temperatures, these polyurethanes are being coated onto various materials to produce breathable fabrics. 43 Biofilters packed with polyurethane foams inoculated with a mixed microbial population were used successfully to adsorb and degrade toluene.…”
Section: Introductionmentioning
confidence: 99%
“…They used five PU/ DMF solutions (3.0, 5.0, 7.0, 10.0, and 12.0 wt%), did not observe jet formation in the PU/ DMF solutions above 12.0 wt% because of the higher viscosity, whereas in a too diluted solution (e.g., <3.0 wt%), the jet broke into droplets and they observed electrospraying instead of electrospinning. Finally, they concluded that uniform PU nanofibers could be produced by using 5.0-7.0 wt% of PU/DMF solutions, applied voltages of 10-15 kV, and feeding rates of 0.06-0.08 mm/min [38]. They also observed that increasing the applied voltage caused stickier fibers [38].…”
Section: Solution and Processing Conditions For Electrospun Pu Nanofimentioning
confidence: 97%
“…Finally, they concluded that uniform PU nanofibers could be produced by using 5.0-7.0 wt% of PU/DMF solutions, applied voltages of 10-15 kV, and feeding rates of 0.06-0.08 mm/min [38]. They also observed that increasing the applied voltage caused stickier fibers [38]. …”
Section: Solution and Processing Conditions For Electrospun Pu Nanofimentioning
confidence: 97%
See 1 more Smart Citation